Rancang Bangun Miniatur Sistem Alat Pengukur Standar Kebisingan Knalpot Sepeda Motor Berbasis Arduino Uno - Budi Santoso; Sayuti Rahman; Arnes Sembiring (LKP Unity Academy, 2023)
Sound is one of the vibrations of an object where the vibration occurs around the air that propagates from all directions where the results vary and the air pressure that applies to the surface of the eardrum that hear. Motorcycles are vehicles that are often heard on the road and there are some motorcycles that have some non-standard exhausts used on these motorcycles. Based on this problem, the author designed a miniature motorcycle exhaust noise measuring device system. Using this design uses Arduino Uno as the center of control rangkian LM393 sound sensor to measure the noise level of the sound produced by the exhaust and OLED displaying the sensor value. For the application of this tool, simply close the sensor to the motorcycle exhaust that will be tested, then the sound value produced by the motorcycle will be displayed on the miniature OLED of the exhaust noise standard measuring device, to determine whether the value produced by the user can see the result on the OLED screen.